2019
DOI: 10.15587/1729-4061.2019.168762
|View full text |Cite
|
Sign up to set email alerts
|

Development of measures to improve milk quality and safety during production

Abstract: Кількість соматичних клітин у молоці корів впливає на якісні показники, ґатунок та безпечність. Рівень в молоці соматичних клітин залежить від стану вим'я у тварин. Тому важливим є вчасно проводити діагностику корів на субклінічний мастит та профілактувати його виникнення. В результаті проведених досліджень визначений гістологічний спектр соматичних клітин у корів української чорно-рябої молочної породи. Експериментально доведено, що мікроорганізми, виділені з шкіри вим'я корів, ідентичні мікрофлорі, яка викли… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 18 publications
3
14
0
4
Order By: Relevance
“…The results of our study are consistent with those reported by other authors, performed earlier [10,15,22,40,41], and complement them. A significant difference in the methodical plan of our study was the opportunity to study not only the rigidity of rubber products but also a series of important technical indicators (coefficient of aging due to tension, relative residual deformation, etc.).…”
Section: Discussion Of Results Of Studying the Qualitative Technical supporting
confidence: 94%
“…The results of our study are consistent with those reported by other authors, performed earlier [10,15,22,40,41], and complement them. A significant difference in the methodical plan of our study was the opportunity to study not only the rigidity of rubber products but also a series of important technical indicators (coefficient of aging due to tension, relative residual deformation, etc.).…”
Section: Discussion Of Results Of Studying the Qualitative Technical supporting
confidence: 94%
“…This will not only protect animals against re-infection with diseases but also increase durability of structures by eliminating biological corrosion [33]. Introduction of bactericidal admixtures reduces microbiological pressure on animals [34].…”
Section: Discussion Of Results Obtained In the Study Of Concretes Witmentioning
confidence: 99%
“…Thus, natural adsorbents along with heavy metals actively excrete essential elements [26], synthetic preparations cause various side effects, which makes their long-term and preventive application impossible [27]. Application of integrated additives with natural components is new and promising in this direction, because it solves all these problems [2,28].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%